A review of diffusion MRI of typical white matter development from early childhood to young adulthood. (8th September 2017) - Lebel, Catherine; Treit, Sarah; Beaulieu, Christian; Leemans, Alexander
Abstract: Understanding typical, healthy brain development provides a baseline from which to detect and characterize brain anomalies associated with various neurological or psychiatric disorders and diseases. Diffusion MRI is well suited to study white matter development, as it can virtually extract individual tracts and yield parameters that may reflect alterations in the underlying neural micro‐structure (e.g. myelination, axon density, fiber coherence), though it is limited by its lack of specificity and other methodological concerns. This review summarizes the last decade of diffusion imaging studies of healthy white matter development spanning childhood to early adulthood (4–35 years). Conclusions about anatomical location, rates, and timing of white matter development with age are discussed, as well as the influence of image acquisition, analysis, age range/sample size, and statistical model. Despite methodological variability between studies, some consistent findings have emerged from the literature. Specifically, diffusion studies of neurodevelopment overwhelmingly demonstrate regionally varying increases of fractional anisotropy and decreases of mean diffusivity during childhood and adolescence, some of which continue into adulthood. While most studies use linear fits to model age‐related changes, studies with sufficient sample sizes and age range provide clear evidence that white matter development (as indicated by diffusion) is non‐linear. Several studies further suggest that maturation in association tracts with frontal‐temporal connections continues later than commissural and projection tracts. The emerging contributions of more advanced diffusion methods are also discussed, as they may reveal new aspects of white matter development. Although non‐specific, diffusion changes may reflect increases of myelination, axonal packing, and/or coherence with age that may be associated with changes in cognition. Abstract : This paper reviews diffusion MRI studies of neurodevelopment in childhood and adolescence. Despite large variation in methods and age ranges, several key themes have emerged: (i) studies overwhelmingly find increases of fractional anisotropy and decreases of mean diffusivity in white matter during development; (ii) changes are widespread throughout the brain; (iii) development is non‐linear, occurring faster at younger ages; and (iv) rates/plateaus are regionally dependent, with the most prolonged development observed in frontal/temporal areas.